Fluorinated triazoles as privileged potential candidates in drug development—focusing on their biological and pharmaceutical properties - Ullah, Ihsan; Ilyas, Muhammad; Omer, Muhammad; Alamzeb, Muhammad; Adnan,; Sohail, Muhammad (Frontiers in Chemistry, 2022)
Fluorinated heterocycles have attracted extensive attraction not only in organic synthesis but also in pharmaceutical and medicinal sciences due to their enhanced biological activities than their non-fluorinated counterparts. Triazole is a simple five-membered heterocycle with three nitrogen atoms found in both natural and synthetic molecules that impart a broad spectrum of biological properties including but not limited to anticancer, antiproliferative, inhibitory, antiviral, antibacterial, antifungal, antiallergic and antioxidant. On the other hand, incorporation of fluorine into triazole and its derivatives has been reported to enhance their pharmacological activity making them promising drug candidates. This mini-review explores the current developments of backbone-fluorinated triazoles and functionalized fluorinated triazoles with established biological activities and pharmacological properties.